Review - Fernandes, Pedro (Aprender, 2023)
Introduction to virtual and augmented reality – chapter 19: EducationTori, R., & da Silva Hounsell, M. (2020). Introduction to virtual and augmented reality. Porto Alegre: Brazilian Computing Society.ISBN: 978-85-7669-446-5Teaching tools have evolved significantly over the years, essentially driven by the growth of information and communication technologies. Teachers and school leaders are permanently looking for new pedagogical solutions that aim to provide students with more appealing, more motivating and, above all, higher quality teaching. In this context, we bring for analysis a book chapter dedicated to the application of virtual reality and augmented reality technologies in education, a topic that, nowadays, is of considerable relevance and relevance.
Keywords: teaching; education; virtual reality; augmented reality